WEBSITE DESIGNING LEARNING OUTCOMES ASSESSMENT OF VOCATIONAL HIGH SCHOOL (SMK) ONLINE USING MACROMEDIA DREAMWEAVER 8 BAKTI IDHATA ON FOUNDATION - Anies Anggriani; Irfan, SKom, MMSI Irfan, SKom, MMSI (Jurnal Sistem Informasi, 2008)
Progressively expanding world of information technology so that all problems can besolved with one computer learning outcomes assessment Vocational High School(SMK) by using the "Learning Outcomes Assessment Website Design VocationalHigh School (SMK) Online, with these applications easier for students andFOUNDATION BAKTI IDHATA can provide or obtain necessary information.